Women's Social Network as Marketing Personnel for Make-up Products in Tanjungpinang City - Firdawati Firdawati; Nanik Rahmawati; Rahma Syafitri (Social Issues Quarterly, 2023)
This study investigates the phenomenon of make-up Sales Promotion Girls (SPGs) in Tanjungpinang City, Riau Islands. These SPGs are commonly found in supermarkets, shops, and crowded areas, promoting various make-up brands. In this current trend, SPGs no longer work alone but instead rely on intermediaries, such as fellow SPGs and friends, to expand their merchandise and reach their sales targets. They collect customers' mobile numbers to promote new products via WhatsApp and distribute brochures while explaining the benefits of their products and offering special discounts. This qualitative descriptive research employed the theory of Fukuyama (2002) and used five informants to investigate the social network of SPGs in Tanjungpinang. The study found that SPGs formed a social network based on family lines, friendships, and fellow SPGs. This network initially served as an economic network and later expanded into a social network, where members cooperate to achieve mutual benefits. The existence of social networks in economic life creates behavioral attachments in interactions or social relations. The informants' values served as rules that must be obeyed to achieve cooperation within the community.